SUBJECTHOOD IN PUNAN TEBUNYAU LANGUAGE: KESUBJEKAN BAHASA PUNAN TEBUNYAU - Achmad Dicky Romadhan; Rita Kumala Sari (LLDIKTI Wilayah X, 2021)
This study aims to see how the subject property in the Dayak Punan Tebunyau language. This subject research is viewed from a grammatical point of view. This research is expected to enrich the subject matter of research, especially in the Dayak Punan Tebunyau language. The data used in this study is oral data. Oral data was taken directly from Punan Tebunyau Dayak native speakers. The data collection technique used in this study is the listening technique and note taking technique. The results of this study explain that the subjecthood in the Dayak language have similarities with the typology of fertility and are in accordance with the various test instruments used.